Um registo de contabilidade medieval do Mosteiro de S. Jorge de Coimbra (1257-1259) - Saul António Gomes (Medievalista)
The author examines and publishes one source of monastic accounting, written between 1257 and 1259, from de monastery of Saint Georges of Coimbra, Order of the regular canons of Saint Augustine. After some considerations about the interest of such documents to the Portuguese medieval history, the author focuses on the conventual history of the regular canons and publishes the source.